Synthesis and characterization of Co-Cu ferrite and bioglass composites for hyperthermia treatment of cancer - Chalisgaonkar V.; Pandey K.; Kumar A.S.; Tripathi R.; Singh S.P.; Pyare R. (My University, 2025)
Novel copper substituted cobalt ferrites with formula CoxCui-xFe204 (where x = 0.2, 0.4, 0.6, 0.8) were prepared through sol-gel auto combustion route and the effect of copper concentration on the structural and magnetic properties was investigated. XRD results revealed the formation of solid solution and the magnetic measurements showed the formation of soft ferrites having less saturation magnetization as compared to CoFe2O4. The bioactive composites were prepared by incorporating the ferrite having optimum magnetic properties pertaining to a soft ferrite with bioactive glass and were sintered at optimized temperature to get maximum densification and the constituent phases in the composite were analyzed by XRD. The bioactive composite comprised of Na2Ca2Si3O9 phase along with the solid solution. In vitro bioactivity of the composite was investigated in simulated body fluid (SBF) in physiological conditions. The precipitation of HCA layer was confirmed by FTIR, SEM and XRD. The magnetic properties and bioactivity of Co-Cu ferrite/ bioglass composite shows that these composites have higher potential for hyperthermia treatment of cancer.